Analisis Kepuasan Kerja di Puskesmas Sukamenanti Kabupaten Pasaman Barat Berdasarkan Pengaruh Lingkungan, Kompensasi Dan Budaya Kerja - Efi Deliza (Universitas Putra Indonesia YPTK Padang, 2022)
This study aims to determine the effect of work environment, compensation, and work culture on employee performance through job satisfaction as an intervening variable at Sukamenanti Public Health Center, West Pasaman Regency. The method used is multiple linear regression analysis and path analysis. by distributing questionnaires to 63 respondents. The results obtained that the work environment has a positive and significant effect on job satisfaction of Sukamenanti Public Health Center employees, West Pasaman Regency. Compensation has a positive and significant effect on the job satisfaction of Sukamenanti Public Health Center employees, West Pasaman Regency. Work culture has a positive and significant effect on job satisfaction of Sukamenanti Public Health Center employees, West Pasaman Regency. The work environment has a negative and insignificant effect on employee performance at Sukamenanti Health Center employees, West Pasaman Regency. Compensation has a positive and insignificant effect on employee performance at Sukamenanti Public Health Center employees, West Pasaman Regency. Work culture has a positive and significant effect on employee performance at Sukamenanti Health Center employees, West Pasaman Regency. Job satisfaction has a positive and significant effect on employee performance at Sukamenanti Health Center employees, West Pasaman Regency. Job satisfaction mediates the effect of the work environment on employee performance because the value of the direct influence is greater than the indirect effect. Job satisfaction mediates the effect of compensation on employee performance because the value of the direct influence is greater than the indirect effect. Job satisfaction mediates the influence of work culture on employee performance because the value of direct influence is greater than indirect influence